Reactivated Recombinant Plasminogen Activator Inhibitor-1 (rPAI-1) Effectively Prevents Thrombolysis In Vivo - Vaughan, Douglas E; Declerck, Paul J; Van Houtte, Elizabeth; De Mol, Maria; Collen, Désiré (Thrombosis and Haemostasis, 1992)
The effects of human recombinant plasminogen activator inhibitor (rPAI-1) on thrombolysis with recombinant tissue-type plasminogen activator (rt-PA) were studied in a rabbit model of jugular vein thrombosis. Two functionally distinct rPAI-1 preparations were used in these experiments, including latent rPAI-1 (~2 units of t-PA neutralizing activity per µg protein) and reactivated rPAI-1 (~150 units/µg).Simultaneous intravenous infusion over 4 h of 1.7 mg/kg of reactivated rPAI-1 (inhibitory capacity ~0.5 mg/kg rt-PA) with 0.5 mg/kg of rt-PA completely prevented lysis of a jugular venous thrombus, whereas an equivalent amount of latent PAI-1 did not significantly influence clot lysis. These findings demonstrate that reactivated human rPAI-1 efficiently neutralizes thrombolysis with rt-PA in vivo. Since previous studies have suggested that elevated endogenous levels of PAI-1 do not attenuate the thrombolytic potency of rt-PA in the endotoxin-treated model, we compared the stability of complexes formed by 125I-rt-PA with reactivated human rPAI-1 and with rabbit PAI-1 in vitro. Our findings indicate that both forms of PAI-1 form SDS-stable complexes following incubation with 125I-rt-PA. Thus, it seems likely that elevated levels of active PAI-1 can negate the thrombolytic effects of rt-PA in vivo and argues against the possibility that t-PA can dissociate from PAI-1 and have its activity restored in the presence of a thrombus. We propose that the present model may be a valuable tool in monitoring and evaluating the in vivo thrombolytic efficacy of various t-PA mutants designed to be less sensitive to the inhibitory effects of PAI-1.